Convergence of Hybrid Fixed Point for a Pair of Nonlinear Mappings in Banach Spaces - G. S. Saluja (International Journal of Analysis and Applications, 2015)
In this paper, we study hybrid fixed point of a modified two-step iteration process with errors for a pair of asymptotically quasi-nonexpansive mapping and asymptotically quasi-nonexpansive mapping in the intermediate sense in the framework of Banach spaces. Also we establish some strong convergence theorems and a weak convergence theorem for the iteration scheme and mappings. The results presented in this paper extend, improve and generalize some previous work from the existing literature.